Revealing Language Choices in Instagram Ads for Local Beauty Brands: Bilingualism Perspective - Juliati, Lilin (Language Horizon: Journal of Language Studies, 2024)
Instagram has now become a fascinating channel for promoting and marketing items. Each business found ways to adopt an array of methods to make its marketing engaging. Nevertheless, in terms of their language choice, this study examines language choice within bilingual Instagram ads, notably for local beauty products, drawing on Fasold's (1984) theory of language choice. It is further supported by Romaine's (1995) theory of code switching and Muysken's (2000) theory of code mixing. This study took a qualitative approach. The study collected data from 10 ad samples spanning the local beauty category. The study demonstrates data points on language choice, starting with several types of code switching (inter-sentential and intra-sentential) and code mixing (insertion, alternation, and congruence). According to this study's findings, intra-sentential switching and insertion were the most popular form language choices. Inter-sentential and alternation were the less prevalent forms.